Costurando a vida com fios de ferro: mulheres negras no limiar entre a vida e a morte em Olhos d’água, de Conceição Evaristo - Cruz, Lorrany Andrade da (2022)
In this dissertation we aim to investigate the female condition of the Black characters in the short story collection Olhos d’água (2014), by Conceição Evaristo, an important writer of Brazilian literature and contemporary Black literature. For this, we analyzed how these Black Brazilian women experience and manifest (talking about manifestation, denunciation), in their time-place, structural oppressions related to colonialism, such as racism, sexism and classism, as observed by Grada Kilomba (2019), considering the way female characters are silenced and how they face this silencing. In the selected short stories, the protagonists are on the threshold between life and death, and in three of them, violence leads to physical death. The concept of poetic Ferocity, created by Franciane Silva (2018), is relevant. This refers to the way violent scenarios in the literature of Afro-Brazilian writers, like Evaristo, are constructed with intense poeticity. From this, we ponder about the latent necropolitics in the reality of these characters and how Evaristo's writing, when speaking of death poetically, humanizing her characters, also speaks about life politics. The preference for this author and her work occurs from a latent need in contemporary times to notice and pay attention to gender issues intersected with issues of race and class without the need to rank them, as Djamila Ribeiro (2019) tells us, and to observe how these categories intersect in the perspective of Black feminism, seeking to break with a split created by an unequal, patriarchal and heterosexist society. The study of the self-representation of the Black woman will allow us to elaborate a reflection on Black feminism and Black literature, as we understand the importance of a Black woman writer, who breaks with the hegemonic discourse and with the colonizing perspective on her body, identity and sexuality (COLLINS apud BERTH, 2018).